The information science in Brazil: Research mapping and institutional outlook - Araújo, Carlos Alberto Ávila; Valentim, Marta Lígia Pomim [UNESP] (My University, 2019)
Objective: Present the Brazilian research in Information Science in this institutional outlook and from the mapping of themes and theories produced by the researchers. Design/Metodology/Approach: For the institutional outlook, we present the performance of two scientific associations: Brazilian Association of Education in Information Science and National Association of Research and Graduation in Information Science. Presents the researched themes by professors and students in the Brazilian graduation scope, more specifically from the National Meeting of Research in Information Science, an annual event that brings together researchers from all over the country and from abroad. The state of art is evidenced in a timeline, through the themes recurrently presented in the aforementioned event. Results/Discussion: It's possible to observe in what way the scientific field has been consolidated, whose discussions related to the country reality focus on problems that motivate the researchers in the research development, that can somehow contribute to the advancement of the scientific field, as well as respond satisfactorily to the demands arising from Brazilian society. Originality/Value: The mapping presented is unprecedented and represents the consolidation of two viewpoints, the institutional and the scientific works produced by the scientific community. At last, we focus in the singularity of the Brazilian Information Science research, the result of the dialogue and appropriation of the USA, Europe and Latin America research elements, as well as a protagonism of autonomy towards an original perspective in the international scene.
A Ciência da Informação no Brasil: Mapeamento da pesquisa e cenário institucional
Keywords: Brazil; Information Science; Scientific Associations; State of Art